Peran Komunitas dalam Mempertahankan Konsistensi Praktik Meditasi: Studi Kasus Komunitas Meditasi Vihara Dhammapala Gerendeng Pulo Kota Tangerang - Vinka Julian Yap; Acep Lauw; Majaputera Karniawan; Rina Mariana; Jenisya Pricillia (STAB Kertarajasa, 2026)
This study aims to analyze the socio-communal mechanisms that support meditation practice consistency and relate them to the concept of Kalyāṇamitta. A qualitative approach with a single-case study design was employed. Data were collected through in-depth interviews with six active practitioners (45–60 minutes each), participant observation over 12 sessions (January–March 2026), and community documentation. Data were analyzed using thematic analysis (Braun), supported by source triangulation (practitioners, monastic administrators, and community records) and methodological triangulation (interviews, observation, and documentation). The findings reveal three key mechanisms: (1) structural accountability through scheduled practice and social expectations, (2) shared narratives that strengthen the meaning of practice, and (3) positive emotional contagion that enhances attachment and engagement. The conclusion shows that practice consistency is determined more by social networks than by individual motivation, in line with the concept of Kalyāṇamitta in the Upaddha Sutta (Saṃyutta Nikāya 45.2), and provides implications for the development of community-based models for meditation practice and training in the context of spiritual education.